Analisis Faktor-Faktor yang Berpengaruh terhadap Motivasi Kerja Petugas Pelaksana Manajemen Terpadu Balita Sakit di Puskesmas - Faridah Faridah (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Integrated Management of Childhood Illness (IMCI) is one of the strategies to improve quality of services for unhealthy infants and children under five years who visit to a health center. To support that program, in June 2008, training of the program was conducted to 42 health centers in Surabaya City in which 23 health centers had implemented the program. Coverage of infants and children under five years who were handled by the program was equal to 10%. The achievement of the work performance could not be separated from the officer’s work motivation of the Integrated Management of Sick Children under Five Years.Objective: to investigate the factors that influences the officer’s work motivation of the Integrated Management of Childhood Illness in the health centers in Surabaya City in year 2009.Method: This was an observational research with survey method and cross-sectional approach. The research instrument used a structured questionnaire which had been examined in terms of the validity and reliability. Data were analyzed using bivariate analysis (Chi Square Test) and multivariate analysis (Logistic Regression Test). Number of sample was 42 respondents who worked as a doctor, a nurse, and a midwife at the health centers in Surabaya City.Result: The result of this research showed that most of the respondents had poor perceptions to the compensation (54.8%), to the work condition (47.6%), to the policy (50.0%), to the supervision (42.9%), to the job (33.3%), and to the work motivation (54.8%). The result of bivariate analysis showed that variables of perception to the work condition, perception to the policy, and perception to supervision had a significant relationship with the officer’s work motivation at the health centers in Surabaya City (p < 0.05). Based multivariate analysis, it showed that variables of perception to the work condition (p value = 0.034 and Exp B = 5.500) and perception to the policy (p value = 0.003 and Exp B = 11.000) together influence the officer’s work motivation at the health centers in Surabaya City.Conclusion: As a suggestion, in terms of the work condition, there should be provided some logistics (medicines, devices, forms, and KNI) before executing the program at the health centers. In terms of the policy, the head of the health centers should make a planning of activities and an understandable regulation. The head of the health centers and a team should make a standard operating procedure of the program.Keywords: work motivation, Integrated Management of Childhood Illness, officer’s work, health centers